Relationship between Family Support and Dietary Compliance in People with Type 2 Diabetes Mellitus - Anita Dwi Ariyani; Ida Ayu Ratna Putri; Badrul Munif; Fany Anitarini (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction:Dietary adherence to type 2 diabetes mellitus suffers is a behavior that must be obeyed. One of the factors that influence dietary adherence is family support because it can lead to patient motivation in implementing dietary adherence. Objectives: This study aimed to determine the relationship between family support and dietary adherence in patients with diabetes mellitus type 2. Methods: This study used a cross-sectional design with a purposive sampling and 72 respondents were taken as a sample. Collecting data using Hensarling Diabetes Family Supposrt Scale (HDFSS) and Perceived Dietary Adherence Questionnaire (PDAQ) then analyzed using the Spearman rank test. Results: Most of the patients (74%) were in the moderate family support category and some of them (57%) were in the moderate diet category. Based on the analysis results obtained P-value 0.014 (P <0.05), which means there is a relationship of 0.290 which indicating low strength relationship. Conclusions: Family support is very important to help sufferers of type 2 diabetes mellitus in carrying out a diet, so families must work together with health workers to increase understanding of the diet of type 2 diabetes sufferers.